An investigation of compliance in Type II diabetic patients attending clinic at Church of Scotland Hospital - S. R. Khoza; W. Kortenbout (AOSIS, 1995)
Thirty Type 11 diabetic patients attending a clinic at a rural hospital were interviewed, using structured interviews and clinic records. The patients' clinic cards were also used to obtain the required information. The study was conducted to identify the factors that lead to non compliance with the recommended treatment regimen, to establish whether diabetic patients are able to keep appointments and to identify factors that influence patients from keeping appointments. Factors that led to non compliance were financial problems and forgetfulness.